2019
DOI: 10.1038/s41598-019-52080-1
|View full text |Cite
|
Sign up to set email alerts
|

Tunable graduated filters based on electrochromic materials for spatial image control

Abstract: Passive graduated filters with fixed absorption profile are currently used in image recording to avoid overexposure. However, a whole set of filters with prescribed gradients is required to cope with changing illumination conditions. Furthermore, they demand mechanical adjustment during operation. To overcome these deficiencies we present a microfabricated active electrochromic graduated filter which combines multiple functionalities: The overall absorbance, the position of medium transmission as well as the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Electrochromic devices (ECDs) have the ability to persistently and reversibly change their optical and electrical properties under the influence of an electrical voltage. [ 1 ] Such a phenomenon has led to the development of their novel transparent applications such as bistable displays, [ 2 ] variable optical attenuators, [ 3 ] plasmonic, or structural color switching, [ 4 ] optical filters, [ 5 ] and, most importantly, electrochromic smart windows for energy‐efficient buildings. [ 6,7 ] The latter class of these ECDs represents an attractive green building technology due to their ability to dynamically control indoor lighting and temperature.…”
Section: Figurementioning
confidence: 99%
“…Electrochromic devices (ECDs) have the ability to persistently and reversibly change their optical and electrical properties under the influence of an electrical voltage. [ 1 ] Such a phenomenon has led to the development of their novel transparent applications such as bistable displays, [ 2 ] variable optical attenuators, [ 3 ] plasmonic, or structural color switching, [ 4 ] optical filters, [ 5 ] and, most importantly, electrochromic smart windows for energy‐efficient buildings. [ 6,7 ] The latter class of these ECDs represents an attractive green building technology due to their ability to dynamically control indoor lighting and temperature.…”
Section: Figurementioning
confidence: 99%
“…Unlike in other EC devices, we did not apply a single potential to the working electrode, but a potential gradient. We demonstrated that the constant current flow along the working electrode between two electrodes created the desired spatial potential distribution φ(x) [18]. We further showed that the spatially varying transmission T can be analytically derived calculating first the potential dependent concentration of reduced, i.e.…”
Section: Introductionmentioning
confidence: 88%
“…[1][2][3] For this situation, a large number of researchers have done many works to "broaden sources of income and reduce expenditure". Electrochromic devices (ECDs) have emerged as the time requirement under this background and are widely used in energy-efficient buildings, [4] bistable displays, [5] variable optical attenuators, [6] optical filters, [7] structural color switching, [8] etc. Electrochromism can be simply defined as the ability of a material to change its optical characters under an applied voltage, where the reversible change of a chemical species occurs between two redox states.…”
Section: Introductionmentioning
confidence: 99%